Speed sensorless sliding mode control of wave power generation based on model predictive strategy - LIANG Haohui; YANG Junhua; YANG Mengli; WANG Chaofan; HUANG Yi; LUO Qi (Diance yu yibiao)
In order to improve the efficiency of direct-drive wave power generation system in complex sea conditions and reduce equipment maintenance costs, a speed sensorless sliding mode control scheme based on model prediction strategy was proposed. Taking the instantaneous power of the generator as the cost function, the optimal electromagnetic force was solved and converted into the reference current. Through vector control and model predictive current control, the current was tracked to capture the maximum power of wave system. The speed direction was judged according to the reference current, and a sliding mode speed observer was designed to realize speed sensorless control. The simulation results show that the system can operate within the safety constraint range by model predictive control strategy, the output power is improved, and the observation accuracy of sliding mode observer keeps high, which can enhance the robustness and safety of the system.